Paths of the technoscene in a pandemic context - Hernández, Moira Gisela (Universidad Nacional del Litoral, 2021)
COVID 19 and the consequent policy of isolation adopted by the countries of the world had different repercussions on social life. In the field of theatre and the performing arts, there are two ways of looking at the same event: a technophobic view that proclaims the nature of theatre as an effective coexistence between actor and audience, vindicating this link almost as an auratic state; and on the other hand, the view of those who see in this situation a possibility of exploring virtual textualities, that is, a theatrical evolution linked to technology. The former argue that this dematerialisation of theatre provokes a loss of meaning that undermines its social character, and the latter, an alternative that has been little explored by the theatre scene, but not for performance or liminal poetics. The work we are analysing, La maldición de la corona by the Catalan group La Fura Dels Baus, considers technology inseparable from social and therefore theatrical evolution. From the most purist theatrical thoughts anchored in coexistence, we move on to the notion of technoscene and the consequent virtual life of artistic works.